Rok 1965 w Indonezji w spektaklach Papermoon Puppet Theatre z Yogyakarty i filmie Scena zbrodni Joshuy Oppenheimera - Lis, Marianna (Studia Azjatystyczne, 2015)
1965 is the date that has been disregarded in the recent history of Indonesia and the world. Gerakan 30 September (30th September Movement), self-appointed organization consisting of representatives of the Indonesian army carried out a failed coup on October 1, 1965, killing six generals. The same day evening the Movement fell and Partai Komunis Indonesia (Indonesian Communist Party) was blamed. In the following weeks communists and their supporters began to be removed from public life being arrested and murdered. The 1965 purges have been read in the West as a victory over communism. In Indonesia they remained taboo for almost half of the century. The paper focuses on showing how the events of 1965 are shown in today's Indonesia and in the word. For Papermoon Puppet Theatre 1965 is a key to understand the past, present and future of their homeland. For Oppenheimer meeting with former criminals has provided an opportunity to make the film about the political system in which genocide was erased from the collective memory of those who survived, and the offenders remain unpunished.